On Susan Wolfs Good-for-Nothings - Bramble, Ben (Ethical theory and moral practice, 2015)
According to welfarism about value, something is good simpliciter just in case it is good for some being or beings. In her recent Presidential Address to the American Philosophical Association, Good-For-Nothings, Susan Wolf argues against welfarism by appeal to great works of art, literature, music, and philosophy. Wolf provides three main arguments against this view, which I call The Superfluity Argument, The Explanation of Benefit Argument, and The Welfarists Mistake. In this paper, I reconstruct these arguments and explain where, in my view, each goes wrong.